Strengthening Students’ Religious Character through the Implementation of School-Based Religious Programs in Junior High Schools - Eka Mustika Riantina (STAI Hubbulwathan Duri, 2025)
Religious character education plays a pivotal role in shaping adolescents' Islamic values and serves as a preventive measure against deviant behavior and promiscuity. This qualitative field study explores the design and implementation of religious programs in schools and their impact on students' character development. Data were collected through observation, interviews, and documentation. The analysis followed four stages: data collection, condensation, presentation, and conclusion drawing. Findings reveal that schools systematically incorporate religious education into both daily routines and periodic activities. These include obligatory prayers, Tadarus (Qur’an recitation), Islamic holiday commemorations, and community-based religious engagements. Such programs nurture spiritual discipline, promote the pursuit of knowledge, and encourage empathy and social responsibility among students. These religious initiatives not only shape students’ moral and spiritual foundations but also act as a buffer against negative influences. They contribute to forming a well-rounded socio-religious identity, enhancing students’ resilience and ethical awareness in contemporary social contexts. The study contributes a new perspective on integrating religious education as a strategic approach to character formation and behavioral prevention. It underscores the significance of a holistic religious education model in reinforcing students' moral integrity and societal engagement.